Overcoming the current system of corporate criminal law - sanctioning corporate citizens: Crime prevention within the limits of the rule of law - Dannecker, Gerhard; Schröder, Thomas (Bribery, fraud, cheating, 2020)
Corporate crime exists in many forms. This treatise shall commence with an example which assesses one of the most notorious manifestations of corporate crime: The problem of corruption seems to be known world-wide in terms of its consequences and extent. In particular, this applies to the upcoming generation of young people entering the professional world.
Gesehen am 03.11.2020